The Relationship between Community Social Capital and Sustainable Tourism in Kare Tourism Village, Madiun Regency - Fanytasari, Anggun Selvanda; Prayitno, Gunawan; Dinanti, Dian; Munada, Wina; Munkombwe, Joshua (Perencanaan Wilayah dan Kota FT UB, 2025)
This study explores the relationship between community social capital and the development of sustainable tourism in Kare Tourism Village, located in Madiun Regency. Kare Village offers various tourism potentials, including natural attractions, cultural heritage, and special interest tourism, all of which can support the village’s economic development. However, the village still faces several challenges, which are particularly low levels of community participation and limited institutional capacity, which hinder optimal tourism development. Using a quantitative approach, data were collected from 335 households through an accidental sampling technique and analyzed using Structural Equation Modeling (SEM). The results show that trust, especially trust in the village government, is the most influential component in shaping social capital in Kare Village. Social capital has been proven to have a significant and positive effect on sustainable tourism, with a path coefficient of 0.729. This indicates that strengthening community social capital in Kare Village could enhance tourism sustainability by up to 72.9%. Among the various indicators of sustainable tourism, marketing through digital platforms is the most influential factor, thus effective tourism management is essential to support the achievement of tourism sustainability. Overall, this study emphasizes the crucial role of social capital in fostering community engagement and ensuring the long-term success of rural tourism. However, the implications of these findings are contextual and most relevant for tourism villages with similar geographical conditions, institutional structures, and socio-economic characteristics as Kare Village.